Coexistence of lung adenocarcinoma and pulmonary tuberculosis within a single lesion: A rare case report. Issue 39 (September 2019) - Byun, Hong Gwon; Yoo, Jin Young; Kim, Sung Jin; Lee, Ok Jun; Yoo, Min Young
Abstract: Rationale: Pulmonary tuberculosis and lung adenocarcinoma are highly prevalent pulmonary diseases associated with high mortality. However, the coexistence of lung cancer and pulmonary tuberculosis is rare. Further, the morphological features of lung cancer with coexisting pulmonary tuberculosis are similar to that of lung cancer without pulmonary tuberculosis, even though the lesion is predominantly cavity. For these reasons, the diagnosis in patients with coexisting lung cancer and pulmonary tuberculosis could be delayed until the advanced stage, and therefore, prognosis in these patients is worse compared with that of lung cancer patients without coexisting pulmonary tuberculosis. Therefore, early diagnosis of the condition is essential for initiating timely and suitable treatment. Patient concerns: A 67-year-old man was detected abnormal finding on chest CT performed outside the hospital during health screening without significant symptom. Diagnoses: Chest CT revealed a 3.2, irregular, enhancing cavitary mass in right lower lobe of lung and PET-CT revealed significant uptake of 18 FDG by the cavitary mass, which was suggestive of lung cancer. Pathology results confirmed a diagnosis of coexisting lung adenocarcinoma and tuberculosis. Interventions and outcome: The patient underwent a right lower lobectomy. No significant complications occurred in a 24 month post-surgery follow-up period Lessons: Although rare, the coexistence of lung adenocarcinoma and tuberculosis within a single lesion can occur. Therefore, early diagnosis of such a lesion is essential to improve the prognosis in affected patients.